The Style of Criminal Act Verses in The Quran and Its Implications for Legal Status Determinationits Implications for Legal Status Determination - Rahman, Muhammad Gazali; Abdullah, Abdullah; Nurkamiden, Sukrin; Jaya M., Umar (Al-Mizan (e-Journal), 2025)
One aspect of law in the Quran is criminal act (jinayat). This law aims to protect, prevent, and avoid criminal acts (jinayat) that may threaten a person's life, property, and honor. Muslims have acknowledged and accepted Islamic law as an absolute truth that must be implemented with the principle of sami‘na wa ata‘na (we hear and we obey), as part of religious practice aimed at achieving well-being in this world and the hereafter. To implement Islamic law properly, a careful understanding and observation of the objectives of sharia, both explicit and implicit, is necessary. This study has two goals: (a) to identify, categorize, and describe the linguistic styles of al-amr (command) and al-nahyu (prohibition) in jinayat verses and their legal implications; and (b) to map and elaborate on the implications of jinayat verses in determining legal status. The styles used in conveying commands and prohibitions in jinayat verses include: (1) commands; a) passive past tense verbs (fi‘il madhi majhul) that contain obligatory demands; b) verbal nouns (masdar), such as "let the one who forgives follow," where the previous imperative form is replaced with compensation; c) imperative sentences using commands verb (fi‘il amr); (2) prohibitions; a) forms that mean “do not”; b) declarative sentences (khabariyah); c) commands (al-amr) that require abstaining from self-harming acts; d) negating expressions. If the divinely prescribed commands and prohibitions are not enforced, perpetrators of crimes will never be deterred, as human-made laws have many weaknesses. Furthermore, if murderers and thieves are merely imprisoned, it could lead to increased hatred.